Investigation of Thermal Cooling Effectiveness of RRVCS for Permafrost Protection under Wide Expressway Embankment - Tao Tang; Tao Ma; Xiaoming Huang; Qiuming Xiao; Hao Wang; Guangji Xu (Advances in Civil Engineering)
In order to improve the thermal stability of wide embankment for the Qinghai-Tibet Expressway (QTE) to be constructed in permafrost zones on Qinghai-Tibet plateau, a new kind of reflective-resistant-ventilated coupling structure (RRVCS) was proposed and designed. A numerical model was then developed through ABAQUS to investigate the influences of RRVCS on the thermal regime of wide embankment. The temperature field and thawing depth of normal wide embankment without protective measures, wide embankment with crushed stone layer, and wide embankment with RRVCS were compared to verify the cooling effectiveness of RRVCS based on numerical analysis. Vermiculite powder has great influences on the thermal property of asphalt mixture, and it can be reduced by 22.8%, 29.5%, 37.3%, and 50.6% after the addition of 4%, 6%, 8%, and 10% vermiculite powder, respectively. Under the same condition, the temperature of RRVCS embankment is the lowest and its thermal stability is the best. Setting crushed stone layer can improve the thermal stability of embankment. However, the improvement is limited for wide embankment with width exceeding 26 m. RRVCS has the best protective effects on the thermal stability of wide embankment and is recommended as a protective measure for wide embankment of expressway in permafrost regions of Qinghai-Tibet Plateau.